Organization of Educational Process of Students with Autism Spectrum Disorders in Russian Federation: Results of all-Russian Monitoring 2018 - Khaustov A.V; Schumskih M.A (Moscow State University of Psychology and Education, 2019)
Presented results of the all-Russian monitoring of the status of education conducted in 2018 by the Ministry of Education and Science of the Russian Federation in common with the Federal Resource Center for the Organization of Comprehensive Support of Children with Autism Spectrum Disorders of the Moscow State University of Psychology and Education. The total number of students with disorders in autism spectrum included in the education system, increased by 43% and amounted to 22953 people compared with 2017 data. Nonuniformity of distribution of students with ASD by the educational level; paucity of children covered by the necessary early intervention programs, secondary and higher professional education are marked. Most of the children (63.9%) with ASD receive educational services at primary general, basic general and secondary general levels. The key problem remains - mass education of children with autism in the context of individualized homeschooling is 34.5% of the total number of students with autism. Staffing issues are expressed in filling the educational process with specialists - 1/3 of children do not receive the necessary psychological support. Only 8.4% of children with autistic disorders are provided with tutor support. Regional resource centers were established in 33 regions of Russia for solving the problems in organization of qualitative education for children and adolescents with autism spectrum disorders.